Qualitative Research = Kvalitativno raziskovanje Different perspectives, emerging trends = Različne perspektive - nastajajoče težnje - Fikfak, Jurij (ZRC SAZU, Založba ZRC, 2004)
The instruments of qualitative methodology are certainly one of the 20th century's greatest achievements among the different research methods in the humanities and social sciences, especially among those that deal with the discourse and world view of the other - the informant, his or her verbal, visual and other messages. In this period several important reflections on the forms and limits of research practice took place: reflections on the informant and the images and theories of the world with which he or she lives and co-creates his or her life~on the ways and means of recording and translating statements or field information into a language that is understandable to academic circles and the interested public~and last but not least, reflections on the researcher's world view with and through which he or she interprets and attempts to understand the culture of the other.